2018
DOI: 10.3390/molecules23082012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quercetin on Proliferation and H2O2-Induced Apoptosis of Intestinal Porcine Enterocyte Cells

Abstract: Weanling stress and toxicosis, which are harmful to the health of pigs’ intestines, are associated with oxidative stress. Quercetin (Que) is a polyphenolic compound that shows good anti-cancer, anti-inflammation and anti-oxidation effects. This study aimed to elaborate whether or not Que promotes IPEC-J2 (intestinal porcine enterocyte cells) proliferation and protects IPEC-J2 from oxidative damage. Thus, we examined the effects of Que on proliferation and H2O2-induced apoptosis in IPEC-J2. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 60 publications
3
63
0
3
Order By: Relevance
“…Increasing concentration of quercetin protects Ishikawa cells after H 2 O 2 treatment, and based on MTT assay results, it could be suggested that quercetin and sodium selenite may have a synergistic effect in protecting the cells against oxidative stress. Similarly, Chen et al (2018) reported that 5 μg/mL quercetin increased cell viability from 20 % up to 80 % in a model of H 2 O 2 -induced oxidative stress at concentration level of 1000 μM in intestinal porcine enterocyte cells (25). Quercetin and sodium selenite combination has a moderate effect on Ishikawa cells' viability exposed to UV radiation and H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Increasing concentration of quercetin protects Ishikawa cells after H 2 O 2 treatment, and based on MTT assay results, it could be suggested that quercetin and sodium selenite may have a synergistic effect in protecting the cells against oxidative stress. Similarly, Chen et al (2018) reported that 5 μg/mL quercetin increased cell viability from 20 % up to 80 % in a model of H 2 O 2 -induced oxidative stress at concentration level of 1000 μM in intestinal porcine enterocyte cells (25). Quercetin and sodium selenite combination has a moderate effect on Ishikawa cells' viability exposed to UV radiation and H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 94%
“…After the solution was fully mixed for 5 minutes, the absorbance of each well was measured at 490 nm by using a microplate reader. The cell viability was calculated according to the previous work …”
Section: Methodsmentioning
confidence: 99%
“…The results revealed that Huangqi Guizhi Wuwu tang had significant therapeutic efficacy in treating peripheral diabetic neuropathy (Pang et al, 2016). Previous studies have shown that quercetin has various biological actions, such as antioxidative and anti-inflammatory effects (Chen et al, 2018), including inhibiting inflammatory cytokines, such as ROS, IFNg, TNF-a, and IL-2 (Meng et al, 2018). Quercetin suppresses the secretion of inflammatory cytokines by regulating transcription factors (NF-kB) (Chen et al, 2005;Potapovich et al, 2011).…”
Section: Introductionmentioning
confidence: 98%